Effect of playing surface on hip and knee kinematics in healthy female soccer players - Fraley, A. L.; Goerger, B. M.; Zinder, S. M.; Fava, N. M.; Lewek, M. D. (Journal of Athletic Training, 2012)
Context: Playing surface is thought to alter lower extremity kinematics and influence the risk of noncontact anterior cruciate ligament (ACL) injury. However, there has been limited research examining the effect of playing surface on hip and knee kinematics. Objective: To determine if hip and knee kinematics during a jump landing cutting task differ between 3rd generation artificial turf and natural grass playing surfaces in unimpaired females. Design: Repeated measures design. Setting: Sport practice fields. Participants: Twenty-seven female Division I varsity and club soccer athletes (17 varsity, 10 club; age = 20.0±1.4 years; height = 167.5±6.5 cm; mass = 65.2±11.1 kg; years playing competitively = 11.6 ±3.3years). Interventions: Participants performed a 90° cutting maneuver immediately after landing from a box jump on natural grass and 3rd generation artificial turf. Hip and knee kinematics were assessed using an electromagnetic motion analysis system. Force sensitive resistors placed in the shoe were used to define initial ground contact. Main Outcome Measures: Hip and knee kinematics in all three planes of motion were assessed at initial contact and peak knee flexion of landing. Excursion was calculated as the angular change from initial contact to the time corresponding with peak knee flexion. Values were averaged across trials for each surface condition. Paired samples t-tests were used to compare joint angles at initial contact and peak knee flexion, as well as excursion values, between conditions. The significance level was set a priori at an alpha of 0.05. Results: Joint angles at eak knee flexion and excursion values differed significantly between surfaces. Specifically, participants showed greater hip adduction (Grass: -3.2±6.6, Turf: 0.8± 7.0; P = 0.005) and less hip external rotation (Grass: -5.6±8.2, Turf: -2.7±7.7; P = 0.007) on artificial turf at peak knee flexion, while exhibiting greater excursion in the frontal plane at the knee on grass (Grass: 9.0±7.4, Turf: 6.5±5.1; P = 0.050). There was no difference between surfaces at initial contact (P > 0.05). At peak knee flexion, there was no difference at the hip in the sagittal plane (P > 0.05) and at the knee (P > 0.05). Excursion values showed no difference at the hip (P > 0.05) and at the knee in the sagittal (P > 0.05) and transverse (P > 0.05) planes. Conclusions: Playing surface significantly affected hip and knee kinematics in this sample of female soccer players. Nevertheless, these findings did not support our expectations that the hip and knee would adopt a position of increased ACL loading while on artificial turf. However, future studies should address the clinical importance of these findings and their influence on the risk for noncontact ACL injury. Such work is important to determine the optimal playing surfaces for practices and games to minimize noncontact injuries.